Developmental Proactivity and Professional Ability as Older Workers' Employability Resources: A Longitudinal Study Explaining Career Events. Issue 2 (2021) - Roobo, Conny; Pruijt, Hans; Koster, Ferry; Leijten, Fenna Ruby Marie
No abstract available